Negative electrode material and preparation method and application thereof

By generating the LiCexPyFz cladding layer in situ on the surface of the graphite negative electrode material, the problem of lithium ion consumption during the charging process of lithium ion batteries is solved, and the charging and discharging efficiency and low-temperature and fast charging performance of the battery are improved.

CN119812255APending Publication Date: 2025-04-11HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935920.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the charging process of lithium-ion batteries, the generation of SEI film will consume some lithium ions, resulting in an irreversible increase in the charging capacity and reducing the first charge and discharge efficiency.

Method used

Graphite is used as the negative electrode material, and a LiCexPyFz coating layer is generated in situ on its surface. The coating layer includes cerium, phosphorus and fluorine elements. By controlling the thickness and composition of the coating layer, the active site and diffusion capacity of lithium ions are enhanced.

Benefits of technology

It improves the first charging and discharging efficiency of lithium-ion batteries, enhances low-temperature performance and fast charging performance, and shows excellent fast charging performance and stable cycling performance under high-speed charging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211507300000121
    Figure BDA0005211507300000121
  • Figure BDA0005211507300000131
    Figure BDA0005211507300000131
  • Figure BDA0005211507300000141
    Figure BDA0005211507300000141
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a preparation method and application thereof, and belongs to the technical field of battery materials. The negative electrode material comprises graphite and a coating layer located on the surface of the graphite, wherein the coating layer comprises a LiCexPyFz material; wherein 0.1 < = x < = 1, 1.5 < = 3y + z < = 4, and 3y + z-3x = 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] When lithium ions begin to embed into the negative electrode, the electrons and lithium ions that reach the negative electrode first react with the electrolyte in contact with the negative electrode, and the organic electrolyte is reduced and decomposed to form a layer of SEI solid electrolyte interface film on the surface of the graphite negative electrode. Only after the formation of a stable SEI film can lithium ions be embedded in the graphite layered structure in large quantities. However, the formation of the SEI film will consume some lithium ions, thereby increasing the irreversible charging capacity of the entire battery and reducing the initial charge and discharge efficiency of the lithium-ion battery. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a negative electrode material.

[0004] The invention also provides a method for preparing the negative electrode material.

[0005] The present invention also provides a negative electrode plate comprising the negative electrode material, which has good energy density, stable performance, good solubility with electrolyte and high ion conductivity.

[0006] The present invention also provides a lithium ion battery comprising the negative electrode plate.

[0007] According to an embodiment of the first aspect of the present invention, a negative electrode material is provided, wherein the negative electrode material comprises graphite and a coating layer located on the surface of the graphite, wherein the coating layer comprises LiCe x P y F z material; wherein 0.1≤x≤1, 1.5≤3y+z≤4, and 3y+z-3x=1. It is understood that x refers to LiCe x P y F z The molar fraction of cerium (Ce) in the molecular formula, y refers to LiCe x P y F z The molar fraction of phosphorus (P) in the molecular formula, z refers to LiCe x P y F z The mole fraction of fluorine (F) in the molecular formula.

[0008] The negative electrode coating material of the present invention is LiCe x P y F zInorganic lithium salts can provide a certain amount of lithium source, thereby improving the initial charge and discharge efficiency of lithium-ion batteries. They can also provide two states of cerium ions (mainly Ce 3+ , Ce 4+ The higher the trivalent cerium content, the more oxygen vacancies there are, the more active sites for lithium ions increase, and Li + The diffusion barrier is lowered, which is beneficial to lithium ion transmission and increased conductivity, thereby improving low-temperature performance and fast charging performance.

[0009] In addition, the negative electrode coating material of the present invention also contains at least one of phosphorus and fluorine. Among them, the phosphorus component and the electrolyte can form a SEI component Li3P. Compared with the common SEI component, Li3P can achieve lower Li + Desolvation barrier and faster Li + Diffusion capacity, under high-speed charging conditions, has excellent fast charging performance, stable cycle performance and high energy density. Fluorine is a fixed element in the SEI film. The LiF-rich SEI film can improve the electrochemical performance of lithium-ion batteries. The uniform and dense fluorinated SEI film formed on the negative electrode surface can promote the uniform deposition of Li and improve the coulombic efficiency and cycle stability of the battery.

[0010] The present invention uses graphite instead of silicon-carbon material. Graphite has higher conductivity than silicon-carbon material. x P y F z After adding inorganic lithium salt materials, the low temperature performance and fast charging performance are significantly improved.

[0011] According to some embodiments of the present invention, the LiCe x P y F z LiCeF4, LiCe 0.4 P 0.6 F 0.4 or Li6Ce2P3, which has a stable crystalline structure, LiCeF4, LiCe 0.4 P 0.6 F 0.4 or Li6Ce2P3 coating layer has uniform thickness, is tightly combined with the graphite material, has good compatibility with the electrolyte, and has good ionic conductivity. According to some preferred embodiments of the present invention, the LiCe x P y F z It is LiCeF4.

[0012] According to some embodiments of the present invention, the LiCe x P y F zThe cerium ions in the material include trivalent cerium ions.

[0013] Ce 3+ The presence of will bring oxygen vacancies, thereby increasing the lithium ion active sites and reducing Li + Diffusion barrier, which is beneficial to lithium ion transport.

[0014] According to some embodiments of the present invention, the negative electrode material satisfies the relationship: 5<(7.8b-5b 2 ) / (7.8a-5a 2 )<390, wherein a represents the mass fraction of the coating layer in the negative electrode material, and b represents the mass fraction of the trivalent cerium ions in the cerium ions.

[0015] Controlling the mass fraction of the coating layer in the negative electrode material and the mass fraction of the trivalent cerium ions in the cerium ions to satisfy the above relationship can not only improve the charging performance of the negative electrode, but also avoid deterioration of high temperature performance.

[0016] According to some embodiments of the present invention, a=0.001-0.074, that is, the coating layer accounts for 0.1%-7.4% of the weight of the negative electrode material. For example, a may be 0.002-0.06, 0.002-0.04, 0.002-0.02, 0.002-0.01, 0.007-0.04, 0.007-0.02, 0.01-0.04.

[0017] According to some embodiments of the present invention, b=0.8-1, that is, the mass fraction of the trivalent cerium ions in the cerium ions is 80%-100%. For example, b may be 0.8-0.95, 0.8-0.9, 0.85-1, 0.85-0.95, 0.85-0.9, 0.9-1, 0.95-1.

[0018] According to some embodiments of the present invention, the mass ratio of the graphite to the coating layer is 1-10:0.01-0.08. x P y F z The weight of LiCe is controlled within this specific range, which can make x P y F z Completely and evenly coat the graphite surface to avoid over-coating or under-coating.

[0019] In the present invention, cerium formate is first coated on the graphite surface and then converted into LiCe in situ. x P y F z , so we can control Ce 3+ The addition amount of graphite and LiCe xP y F z The proportion of the cladding.

[0020] According to some embodiments of the present invention, the coating layer has a thickness of 2 to 50 nm, such as 5 to 25 nm.

[0021] According to some embodiments of the present invention, the graphite is in a granular form, and further, the particle size of the graphite particles is 6 to 15 μm, such as 8 to 12 μm.

[0022] According to some embodiments of the present invention, the negative electrode material is in a granular form, and further, the D50 of the negative electrode material particles is 8 to 15 μm.

[0023] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing the negative electrode material, comprising the following steps:

[0024] At least one of a phosphorus source and a fluorine source, graphite coated with cerium formate, and a lithium source are mixed and calcined to coat the surface of the graphite with LiCe x P y F z Material, that is, the negative electrode material.

[0025] The cerium formate coated on the graphite surface can better react with the lithium source, fluorine source and / or phosphorus source to form a LiCe with uniform thickness. x P y F z The coating layer is firmly bonded to the graphite material and is not easy to fall off; at the same time, coating it on the surface of natural graphite can not only improve the compatibility with the electrolyte, but also achieve good electrochemical performance. In addition, cerium formate (especially compared with traditional cerium dioxide) has a high oxygen vacancy content, which can increase the oxygen vacancy content of the material, thereby increasing the lithium ion active sites and reducing Li + The diffusion barrier is conducive to the transmission of lithium ions, and its electrical conductivity is also greater than that of cerium dioxide.

[0026] Taking the simultaneous presence of a phosphorus source and a fluorine source as an example, the reaction process of cerium formate with lithium carbonate (as an exemplary lithium source) and nitrogen fluoride (as an exemplary fluorine source) and phosphorus (as a phosphorus source) is shown in the following formula:

[0027] Δ

[0028] Ce(HCOO)3+Li2CO3+P+NF3→LiCe x P y F z +CO2+N2+H2O.

[0029] According to some embodiments of the present invention, the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, iron phosphate, and lithium dihydrogen phosphate.

[0030] According to some embodiments of the present invention, the fluorine source is selected from at least one of nitrogen fluoride and sodium fluoride.

[0031] According to some embodiments of the present invention, the lithium source is selected from at least one of lithium carbonate, lithium acetate, lithium nitrate, lithium dihydrogen phosphate, lithium phosphate, and lithium hydroxide.

[0032] According to some embodiments of the present invention, the calcination temperature is 300-500°C.

[0033] According to some embodiments of the present invention, the calcination time is 4 to 8 hours.

[0034] According to some embodiments of the present invention, the calcination is performed under an inert atmosphere, which includes but is not limited to one or more of argon, nitrogen, helium or hydrogen.

[0035] According to some embodiments of the present invention, the mass ratio of the lithium source to the cerium formate coated graphite is 1:15-25.

[0036] According to some embodiments of the present invention, the mass ratio of the phosphorus source to the cerium formate-coated graphite is 1:15-25.

[0037] According to some embodiments of the present invention, the fluorine source is a gas, and the ratio of the ventilation volume of the fluorine source to the mass of the cerium formate-coated graphite is 1.5-4 mL / min:1 kg. The present invention does not impose any particular limitation on the ventilation time of the fluorine source. For example, the ventilation time may be 4-8 h.

[0038] According to some embodiments of the present invention, the cerium formate-coated graphite is prepared by the following steps (a) or (b), wherein:

[0039] Step (a) comprises: adding a cerium source into a dispersion of graphite, filtering and drying after a hydrothermal reaction, to obtain;

[0040] Step (b) comprises: filtering, drying and heating the dispersion containing the cerium source after hydrothermal treatment to obtain cerium formate; mixing the cerium formate with graphite and ball milling to obtain the product.

[0041] The reaction chemical formula for synthesizing cerium formate of the present invention is as follows:

[0042]

[0043] Compared with the ball milling method in step (b), in step (a), a uniform cerium formate coating layer rich in trivalent cerium is first formed on the surface of the graphite material by a hydrothermal method, and then LiCe is generated in situ. x P y F z The coating layer makes the coating layer thickness uniform, and the coating layer thickness is uniform. It can not only adhere to the surface of the graphite material during the battery cycle to maintain the stability of the material (improve the bonding firmness between the coating layer and the graphite material), thereby improving the cycle performance of the graphite, but also provide multi-dimensional lithium insertion channels to improve the rate performance of the graphite material, which is beneficial to the hot box, storage, low-temperature discharge and other performances, and the electrochemical performance is better.

[0044] According to some embodiments of the present invention, the cerium source is selected from at least one of cerium nitrate, cerium sulfate, cerium acetate and cerium chloride.

[0045] According to some embodiments of the present invention, the mass ratio of the graphite to the cerium source is 40-100:1.

[0046] According to some embodiments of the present invention, the drying temperature is 70-100°C.

[0047] According to some embodiments of the present invention, the drying time is 12 to 36 hours.

[0048] According to some embodiments of the present invention, in step (a), the graphite dispersion comprises graphite and a solvent, and the solvent is selected from: DMF, water or a mixture thereof. According to some embodiments of the present invention, the mass ratio of the graphite to the solvent is 1:4-8.

[0049] According to some embodiments of the present invention, in step (a), the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 8-15 h.

[0050] According to some embodiments of the present invention, in step (b), the dispersion containing the cerium source comprises a cerium source and a solvent, and the solvent is selected from DMF, water or a mixture thereof. According to some embodiments of the present invention, the mass ratio of the cerium source to the solvent is 1:200-600.

[0051] According to some embodiments of the present invention, in step (b), the temperature of the hydrothermal treatment is 70 to 100° C., and the time of the hydrothermal treatment is 8 to 15 hours.

[0052] According to some embodiments of the present invention, in step (b), the heating temperature is 450-600° C., and the heating time is 4-8 hours.

[0053] According to some embodiments of the present invention, in step (b), the ball milling speed is 200-400 rpm, and the ball milling time is 8-12 h.

[0054] According to an embodiment of the third aspect of the present invention, there is provided a negative electrode plate comprising the above-mentioned negative electrode material.

[0055] According to some embodiments of the present invention, the negative electrode plate further includes a conductive agent and a binder, and the mass ratio of the negative electrode material to the conductive agent and the binder is 95-99:0.5-2.5:0.5-2.5.

[0056] According to some embodiments of the present invention, the conductive agent is selected from at least one of carbon black conductive agent SP, carbon nanotube CNT, carbon nanofiber, flake graphite, carbon dots, and graphene. Preferably, the conductive agent is a mixture of SP and CNT in a mass ratio of 9:1.

[0057] According to some embodiments of the present invention, the binder is selected from at least one of styrene-butadiene rubber SBR, polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate PAALi, polyimide, polyamide-imide, polyvinylidene fluoride PVDF, polyvinyl alcohol PVA, polytetrafluoroethylene PTFE, polyvinyl butyral PVB, water-based acrylic resin, carboxymethyl cellulose CMC, and sodium carboxymethyl cellulose CMC-Na. Preferably, the binder is a mixture of SBR and PAALi in a mass ratio of 1:3-4.

[0058] According to an embodiment of the fourth aspect of the present invention, a method for preparing the above-mentioned negative electrode sheet is provided, comprising the following steps:

[0059] A negative electrode slurry is provided, wherein the raw materials for preparing the negative electrode slurry include the negative electrode material, and the negative electrode slurry is coated on at least one side of the surface of the current collector, and the negative electrode sheet is obtained after drying.

[0060] According to some embodiments of the present invention, the current collector is selected from at least one of copper foil, foam copper, nickel foil, foam nickel, stainless steel foil, tin foil, and a composite current collector.

[0061] According to an embodiment of the fifth aspect of the present invention, there is provided a lithium-ion battery, comprising the above-mentioned negative electrode plate, positive electrode plate, separator and electrolyte.

[0062] The present invention does not impose any special restrictions on the positive electrode plate, as long as the purpose of the present invention can be achieved. For example, the positive electrode plate includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The present invention does not impose any special restrictions on the positive current collector. For example, the positive current collector may include aluminum foil or aluminum alloy foil. The positive active material layer contains positive active material. The present invention does not impose any special restrictions on the type of positive active material. For example, in some embodiments, the secondary battery is a lithium-ion battery, and the positive active material may include lithium nickel cobalt manganese oxide (NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. In other embodiments, the secondary battery is a sodium-ion battery, and the positive active material may include Na[Ni 1 / 3Fe 1 / 3 Mn 1 / 3 ]O2. The present invention does not impose any special restrictions on the thickness of the positive electrode current collector and the positive electrode active material layer. For example, the thickness of the positive electrode current collector is 5μm to 20μm, preferably 6μm to 18μm. The thickness of the single-sided positive electrode active material layer is 30μm to 120μm. The positive electrode active material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. The positive electrode active material layer of the present invention may also include a conductive agent and a binder. The selection of the conductive agent and the binder is as described above, and may be the same as or different from that of the negative electrode active material layer.

[0063] The present invention does not impose any special restrictions on the electrolyte, and those skilled in the art can select according to actual needs, for example, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), carbon At least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present invention has no restrictions on the type of lithium salt. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present invention has no particular limitation on the concentration of lithium salt in the electrolyte, for example, the concentration of lithium salt is 1.0 mol / L to 2.0 mol / L. Optionally, the electrolyte of the present invention may further include additives, which may be selected from positive electrode film-forming additives, negative electrode film-forming additives, and circulation-improving and low-temperature additives, but are not limited thereto.

[0064] The present invention does not impose any particular restrictions on the diaphragm, for example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. The present invention does not impose any particular restrictions on the thickness of the diaphragm, for example, the thickness of the diaphragm may be 5 μm to 500 μm.

[0065] According to some embodiments of the present invention, there are at least the following beneficial effects:

[0066] Compared with the prior art, the coating material of the present invention contains Ce and P and / or F components, wherein the phosphorus component and the electrolyte can form a SEI component Li3P. Compared with the common SEI component, Li3P can achieve lower Li + Desolvation barrier and faster Li +Diffusion capacity, under high-speed charging conditions, it has excellent fast charging performance, stable cycle performance and high energy density. The addition of fluorine is also beneficial to improve the electrochemical performance of lithium-ion batteries. 3+ The presence of will bring oxygen vacancies, thereby increasing the lithium ion active sites and reducing Li + Diffusion barrier, which is beneficial to lithium ion transport.

[0067] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0069] Figure 1 This is a SEM image of the negative electrode material in Example 1. DETAILED DESCRIPTION

[0070] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0071] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0072] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±10%, for example, about 100 is actually 100±10%×100.

[0073] Unless otherwise specified, the “particle size” in the present invention refers to the D50 particle size.

[0074] In the description of the present invention, the description with reference to the terms "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0075] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0076] Example 1

[0077] This embodiment provides a negative electrode material, including graphite and a LiCeF4 coating layer generated in situ on the graphite surface, wherein the weight ratio of graphite to LiCeF4 coating layer is 5:0.04, that is, the coating layer accounts for 0.0079 of the mass fraction of the negative electrode material. The D50 particle size of the negative electrode material is about 11 μm, wherein the thickness of the coating layer is about 12.5 nm. Figure 1 As shown in , the surface of the coated graphite presents a smooth morphology, indicating that the thickness of the coating layer is uniform.

[0078] This embodiment also provides a method for preparing the above-mentioned negative electrode material, comprising:

[0079] S1. Add 5 kg of graphite (particle size of about 10 μm) into 25 kg of DMF aqueous solution (DMF and water are mixed at v / v=1:1), stir and disperse for 30 minutes to obtain a graphite dispersion;

[0080] S2, adding 0.0778 kg of cerium nitrate hexahydrate to the graphite dispersion obtained in step S1, stirring and dispersing for 30 minutes to obtain a cerium-containing graphite dispersion;

[0081] S3, hydrothermally treating the cerium-containing graphite dispersion obtained in step S2 at 180° C. for 12 h, filtering it with suction, and drying it at 85° C. for 24 h to obtain cerium formate-coated graphite;

[0082] S4. The cerium formate-coated graphite obtained in step S3 is mixed with lithium carbonate in a mass ratio of 20:1, and an inert gas (such as argon) and nitrogen fluoride (NF3) are introduced at the same time, wherein the flow rate of the inert gas is 7.5 mL / min, and the flow rate of the nitrogen fluoride is 15 mL / min; after ventilation for 0.5 h, the mixture is heated to 350 ° C and calcined for 6 h, and the ventilation and grinding are continued during the calcination process to obtain a negative electrode material.

[0083] Example 2

[0084] This embodiment provides a negative electrode material, which is different from Embodiment 1 only in that the weight ratio of graphite to LiCeF4 coating layer is 5:0.08, that is, the mass fraction of the coating layer in the negative electrode material is 0.0157.

[0085] This embodiment also provides a method for preparing the negative electrode material, which is carried out with reference to that in Embodiment 1, except that the amount of cerium nitrate hexahydrate added in step S2 is 0.156 kg.

[0086] Example 3

[0087] This embodiment provides a negative electrode material, which is different from Embodiment 1 only in that the weight ratio of graphite to LiCeF4 coating layer is 1:0.04, that is, the mass fraction of the coating layer in the negative electrode material is 0.0385.

[0088] This embodiment also provides a method for preparing the negative electrode material, which is carried out with reference to that in Embodiment 1, except that the amount of graphite added in step S1 is 1 kg.

[0089] Example 4

[0090] This embodiment provides a negative electrode material, which is different from Embodiment 1 only in that the weight ratio of graphite to LiCeF4 coating layer is 5:0.8, that is, the mass fraction of the coating layer in the negative electrode material is 0.1379.

[0091] This embodiment also provides a method for preparing the negative electrode material, which is carried out with reference to that in Example 1, except that the amount of cerium nitrate hexahydrate added in step S2 is 1.56 kg.

[0092] Example 5

[0093] This embodiment provides a negative electrode material, which is different from Embodiment 1 only in that the weight ratio of graphite to LiCeF4 coating layer is 5:0.01, that is, the mass fraction of the coating layer in the negative electrode material is 0.0020.

[0094] This embodiment also provides a method for preparing the negative electrode material, which is carried out with reference to that in Example 1, except that the amount of cerium nitrate hexahydrate added in step S2 is 0.0195 kg.

[0095] Example 6

[0096] This embodiment provides a negative electrode material, which includes graphite and a Li6CeP3 coating layer generated in situ on the graphite surface, and the weight ratio of graphite to Li6CeP3 coating layer is 5:0.04, that is, the mass fraction of the coating layer in the negative electrode material is 0.0079.

[0097] This embodiment also provides a method for preparing the above-mentioned negative electrode material, which is carried out with reference to that in Example 1, except that: in S4, the cerium formate-coated graphite obtained in step S3 is mixed with lithium carbonate and red phosphorus in a mass ratio of 20:1:1, heated and calcined at 450°C for 6 hours in an inert gas environment, and ground to obtain the negative electrode material.

[0098] Similarly, negative electrode materials with a weight ratio of graphite to LiCeF4 coating layer of 1:0.04, 5:0.08, 5:0.8, and 5:0.01 can be prepared.

[0099] Example 7

[0100] This embodiment provides a negative electrode material, which includes graphite and LiCe generated in situ on the surface of graphite. 0.4 P 0.6 F 0.4 Coating layer, graphite and LiCe 0.4 P 0.6 F 0.4 The weight ratio of the coating layer is 5:0.04, that is, the mass fraction of the coating layer to the negative electrode material is 0.0079.

[0101] This embodiment also provides a method for preparing the above-mentioned negative electrode material, which is carried out in accordance with Example 1, except that: in S4, the cerium formate-coated graphite obtained in step S3 is mixed with lithium carbonate and red phosphorus in a mass ratio of 20:1:1, and an inert gas and nitrogen fluoride are introduced at the same time, wherein the flow rate of the inert gas is 7.5 mL / min, and the flow rate of the nitrogen fluoride is 15 mL / min; after ventilation for 0.5 h, the mixture is heated to 450° C. and calcined for 6 h, and ventilation and grinding are continued during the calcination process to obtain the negative electrode material.

[0102] Similarly, graphite and LiCe can be prepared 0.4 P 0.6 F 0.4 The weight ratios of the coating layers are 1:0.04, 5:0.08, 5:0.8, and 5:0.01 for the negative electrode materials.

[0103] Example 8

[0104] This embodiment provides a negative electrode material, which is different from Embodiment 1 only in that cerium formate is first synthesized and then coated on the graphite surface by ball milling.

[0105] The preparation method of the negative electrode material is as follows:

[0106] S1. Add 0.0778 kg of cerium nitrate hexahydrate to 25 kg of DMF aqueous solution (DMF and water are mixed at v / v=1:1), stir and disperse for 30 minutes to obtain a cerium-containing dispersion;

[0107] S2, hydrothermally treating the cerium-containing dispersion obtained in step S1 at 80° C. for 12 h, filtering, drying at 85° C. for 24 h, and heating at 500° C. for 6 h to obtain cerium formate;

[0108] S3, mixing the cerium formate obtained in step S2 with 5 kg of graphite, and ball milling, controlling the ball milling speed to 250 rpm, and the ball milling time to 11 h, to obtain cerium formate-coated graphite;

[0109] S4. The cerium formate-coated graphite obtained in step S3 is mixed with lithium carbonate in a mass ratio of 20:1, and an inert gas and nitrogen fluoride are introduced at the same time, wherein the flow rate of the inert gas is 7.5 mL / min, and the flow rate of the nitrogen fluoride is 15 mL / min; after ventilation for 0.5 h, the mixture is heated to 350 ° C and calcined for 6 h, with continuous ventilation and grinding during the calcination process to obtain a negative electrode material.

[0110] Comparative Example 1

[0111] This comparative example provides a negative electrode material, which is different from Example 1 only in that it does not contain a LiCeF4 coating layer, that is, the mass fraction of the coating layer in the negative electrode material is 0.

[0112] This comparative example also provides a method for preparing the negative electrode material, which is carried out with reference to Example 1, except that cerium nitrate hexahydrate is not added in step S2.

[0113] Comparative Example 2

[0114] This comparative example provides a negative electrode material, which differs from Example 1 in that CeO2 is in-situ generated on the graphite surface instead of LiCeF4.

[0115] The preparation method of the negative electrode material is as follows:

[0116] S1. Add 5 kg of graphite (particle size of about 10 μm) into 25 kg of aqueous solution, stir and disperse for 30 minutes to obtain a graphite dispersion;

[0117] S2, adding 0.0778 kg of cerium nitrate hexahydrate to the graphite dispersion obtained in step S1, stirring and dispersing for 30 minutes to obtain a cerium-containing graphite dispersion;

[0118] S3. The cerium-containing graphite dispersion obtained in step S2 is heated at 80° C. for 12 h, filtered, dried at 85° C. for 24 h, and then calcined at 500° C. for 6 h to obtain CeO2-coated graphite.

[0119] Comparative Example 3

[0120] This comparative example provides a negative electrode material, which is different from Example 1 in that lithium cerate is in-situ generated on the graphite surface instead of LiCeF4.

[0121] The preparation method of the negative electrode material is as follows: refer to Example 1, the only difference is that: in S4, the cerium formate-coated graphite obtained in step S3 is mixed with lithium carbonate in a mass ratio of 20:1, heated to 350°C in an inert atmosphere, calcined for about 6 hours, and ground to obtain the negative electrode material.

[0122] Comparative Example 4

[0123] This comparative example provides a negative electrode material, which is different from Example 1 in that cerium fluoride is in-situ generated on the graphite surface instead of LiCeF4.

[0124] The preparation method of the negative electrode material is as follows: refer to Example 1, the only difference is that: in S4, an inert gas and nitrogen fluoride are simultaneously introduced into the cerium formate-coated graphite obtained in step S3, wherein the flow rate of the inert gas is 7.5 mL / min, and the flow rate of the nitrogen fluoride is 15 mL / min; after ventilation for 0.5 h, heating to 350° C. and calcining for about 6 h, continuously ventilating during the calcination process, grinding, and obtaining the negative electrode material.

[0125] Application Examples

[0126] This application example provides a negative electrode plate, comprising the above-mentioned negative electrode material.

[0127] The steps of preparing the negative electrode plate include:

[0128] The above-mentioned negative electrode material is mixed with a conductive agent (SP and CNT are mixed in a mass ratio of 0.45:0.05) and a binder (SBR and PAALi are mixed in a mass ratio of 0.5:1.8) in a weight ratio of 97.7:1.1:1.2 to prepare an active material slurry, which is evenly coated on the negative electrode copper foil collector, and then cold pressed and stripped to obtain a negative electrode sheet.

[0129] Furthermore, this application example also provides a lithium-ion battery, including an electrolyte, a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0130] The preparation steps of the lithium-ion battery include:

[0131] Preparation of positive electrode:

[0132] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0133] Preparation of electrolyte:

[0134] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0135] Isolation film:

[0136] Polyethylene film is selected as the isolation film.

[0137] Preparation of lithium-ion batteries:

[0138] The positive electrode sheet, negative electrode sheet and separator are wound into a battery cell, and the positive electrode tab and negative electrode tab are connected to the positive and negative electrodes of the battery cell by ultrasonic welding. Then, they are placed in an aluminum plastic film and injected with electrolyte. The battery after injection is formed and the gas chamber is cut.

[0139] Test Case

[0140] 1. Ce 3+ content

[0141] The test was carried out by weighing method, and the test results are shown in Table 1.

[0142] Table 1

[0143]

[0144]

[0145] It can be seen from Table 1 that the trivalent cerium content in Example 1 is the highest; by comparing Example 1 with Examples 2 to 5, it can be seen that too high or too low an amount of Ce ions added will reduce the trivalent cerium content; by comparing Example 1 with Comparative Example 2, it can be seen that the trivalent cerium content in the CeO2 coating layer is much lower than the trivalent cerium content in the cerium formate coating layer.

[0146] 2. Low temperature discharge performance

[0147] The test method is as follows:

[0148] S1. All charging should be carried out at an ambient temperature of 25℃±3℃, and discharging should be carried out at each set temperature; 3.0V, 3.2V, and 3.4V capacities are given simultaneously;

[0149] S2, charge to 4.53V at 0.5C constant current and constant voltage, cut-off rate 0.02C;

[0150] S3, shelving: time 5min;

[0151] S4, discharge at a constant current of 0.2C, with a cut-off voltage of 3V, and take this capacity as the normal temperature discharge capacity, i.e., the initial capacity;

[0152] (1) Shelf time: 5 minutes;

[0153] (2) Temperature box configuration: temperature 25℃;

[0154] (3) Shelf time: 120 min;

[0155] (4) Charge to 4.50V at 0.5C constant current and constant voltage, with a cut-off rate of 0.02C;

[0156] (5) Shelf: 5 min;

[0157] (6) Temperature box configuration: temperature -10℃;

[0158] (7) Shelf: 120 min;

[0159] (8) Discharge at a constant current of 0.2C and a cut-off voltage of 3V;

[0160] (9) Shelf: 5 min;

[0161] (10) Temperature box configuration: temperature 25°C;

[0162] (11) Shelf: 120 min;

[0163] (12) Charge to 4.50 V at 0.5 C constant current and constant voltage, with a cut-off rate of 0.02 C;

[0164] (13) Shelf: 5 min;

[0165] (14) Temperature box configuration: temperature -20℃;

[0166] (15) Shelf: time 120mi;

[0167] (16) Discharge at a constant current of 0.2C and a cut-off voltage of 3V;

[0168] (17) Shelf: 5 min;

[0169] (18) Temperature box configuration: temperature 25°C;

[0170] (19) Shelf: time 120 min;

[0171] (20) Charge to 4.50 V at 0.5 C constant current and constant voltage, with a cut-off rate of 0.02 C;

[0172] (21) Shelf: 5 min;

[0173] (22) End;

[0174] Low temperature discharge performance = discharge capacity at this temperature / discharge capacity at 25°C.

[0175] The test results are shown in Table 2.

[0176] Table 2

[0177]

[0178] In Table 2, by comparing Examples 1 to 8 with Comparative Example 1, it can be seen that the coated LiCeF4, Li6CeP3, LiCe 0.4 P 0.6 F 0.4 The low-temperature discharge performance of the graphite is greatly improved; by comparing Example 1 and Example 8, it can be seen that the coating by the in-situ method is more conducive to significantly improving the low-temperature discharge performance than the coating by the ball milling method. This is because the thickness of the coating layer by the in-situ method is uniform. Coating it on the surface of the graphite can not only improve its compatibility with the electrolyte, but also firmly combine with the graphite material, not easy to fall off, and has good electrochemical performance; by comparing Example 1 and Comparative Example 2, it can be seen that the higher the trivalent cerium content, the better the low-temperature performance, which shows that the trivalent cerium can increase the oxygen vacancy content of the material, thereby increasing the lithium ion active sites and reducing Li + Diffusion barrier, which is beneficial to lithium ion transport.

[0179] 3. RT lithium precipitation

[0180] The test method for RT lithium precipitation is as follows: RT2.8C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and set aside for 5min; ② Discharge to 3V at 0.7C constant current, set aside for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.8C constant current and constant voltage, cut-off rate 0.025C, and set aside for 5min; ⑤ Disassemble the interface; RT2.6C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and set aside for 5min; ② Discharge to 3V at 0.7C constant current, set aside for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.6C constant current and constant voltage, cut-off rate 0.025C, and set aside for 5min; ⑤ Disassembly interface; RT2.4C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.4C constant current and constant voltage, cutoff rate 0.025C, and let it stand for 5min; ② Discharge to 3V at 0.7C constant current, and let it stand for 5min; ③ Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.4C constant current and constant voltage, cutoff rate 0.025C, and let it stand for 5min; ⑤ Disassembly interface; RT2.6C2C / 0.7C lithium precipitation: ① Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and let it stand for 5min; ② Discharge to 3V at 0.7C constant current, and let it stand for 5min; Repeat steps ① to ② for a total of 49 times; ④ Charge to 4.5V at 2.2C constant current and constant voltage, cutoff rate 0.025C, and let it stand for 5min; ⑤ Disassembly interface.

[0181] The test results are shown in Table 3.

[0182] Table 3

[0183]

[0184]

[0185] In Table 3, by comparing Examples 1 to 8 with Comparative Examples 1 to 4, it can be seen that LiCeF4, Li6CeP3, LiCe 0.4 P 0.6 F 0.4 The coating can improve the graphite dynamics, which is due to LiCeF4, Li6CeP3, LiCe 0.4 P 0.6 F 0.4 Inorganic lithium salts can provide multi-dimensional lithium insertion channels to improve the rate performance of graphite materials, and trivalent cerium can increase the oxygen vacancy content of the material, thereby increasing the lithium ion active sites and reducing Li +Diffusion barrier is beneficial to lithium ion transmission; by comparing Example 1 and Example 8, it can be seen that the in-situ coating is more helpful to improve the graphite dynamics than the ball milling coating. This is because the coating layer synthesized by the in-situ method has a uniform thickness, is firmly bonded to the graphite material, is not easy to fall off, and has good electrochemical performance.

[0186] The above content describes the embodiments of the present invention in detail in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes graphite and a coating layer located on the surface of the graphite, wherein the coating layer includes LiCe x P y F z Material; wherein 0.1≤x≤1, 1.5≤3y+z≤4, and 3y+z-3x=1.

2. The negative electrode material according to claim 1, characterized in that The LiCe x P y F z The cerium ions in the material include trivalent cerium ions.

3. The negative electrode material according to claim 2, characterized in that The negative electrode material satisfies the relationship: 5<(7.8b-5b 2 ) / (7.8a-5a 2 )<390, wherein a represents the mass fraction of the coating layer in the negative electrode material, and b represents the mass fraction of the trivalent cerium ions in the cerium ions.

4. The negative electrode material according to claim 2, characterized in that The mass fraction of the coating layer to the negative electrode material is 0.1% to 7.4%, and / or the mass fraction of the trivalent cerium ions to the cerium ions is 80% to 100%.

5. A method for preparing a negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: At least one of a phosphorus source and a fluorine source, graphite coated with cerium formate, and a lithium source are mixed and calcined to coat the surface of the graphite with LiCe x P y F z Material, that is, the negative electrode material.

6. The preparation method according to claim 5, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium acetate, lithium nitrate, lithium dihydrogen phosphate, lithium phosphate, and lithium hydroxide; And / or, the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, iron phosphate, and lithium dihydrogen phosphate; And / or, the fluorine source is selected from at least one of nitrogen fluoride and sodium fluoride; And / or, the calcination temperature is 300-500°C; And / or, the calcination time is 4 to 8 hours.

7. The preparation method according to claim 5, characterized in that: The cerium formate-coated graphite is prepared by the following steps (a) or (b), wherein: Step (a) comprises: adding a cerium source into a dispersion of graphite, filtering and drying after a hydrothermal reaction, to obtain; Step (b) comprises: filtering, drying and heating the dispersion containing the cerium source after hydrothermal treatment to obtain cerium formate; mixing the cerium formate with graphite and ball milling to obtain the product.

8. The preparation method according to claim 7, characterized in that: The cerium source is selected from at least one of cerium nitrate, cerium sulfate, cerium acetate and cerium chloride; And / or, the mass ratio of the graphite to the cerium source is 4 to 10:1; And / or, the temperature of the hydrothermal reaction is 160-200°C; And / or, the hydrothermal reaction time is 8 to 15 hours; And / or, the temperature of the hydrothermal treatment is 70-100°C; And / or, the hydrothermal treatment time is 8 to 15 hours; And / or, the heating temperature is 450-600°C; And / or, the heating time is 4 to 8 hours.

9. A negative electrode plate, characterized in that: The invention comprises the negative electrode material as described in any one of claims 1 to 4 or the negative electrode material prepared by the preparation method as described in any one of claims 5 to 8.

10. A lithium ion battery, characterized in that Including the negative electrode sheet as described in claim 9.